Independent Smallholder Oil Palm Expansion and Its Impact On Deforestation: Case Study in Kampar District, Riau Province, Indonesia - Erniwati Erniwati; Ervizal AM. Zuhud; Iswandi Anas; Arzyana Sunkar; Yanto Santosa (Institut Pertanian Bogor (IPB University), 2017)
Independent smallholders who manage their own oil palm plantations without receiving technical assistance and agricultural inputs from oil palm estates or government have been increasing rapidly in Indonesia in recent years. However the magnitude of their impacts on tropical forest deforestation remains largely unevaluated. The objective of this study was to explore the history of land use, and the changes in land cover and status since the onset of oil palm plantation activities. The study was conducted from March to April 2016. Surveys were carried out in 30 ha of independent smallholder oil palm in Kampar District, Riau Province. To identify the land status, the Agreed functional forest classification (TGHK) and Provincial land use planning (RTRWP) maps were overlaid on images of the area of independent smallholder oil palm. Landsat images three years before oil palm was established were used to assess forest cover changes. Furthermore, oil palm smallholders and elders of the local community in the research area were interviewed to identify land use prior to oil palm. Our results showed that, based on land status, 47% of the area of independent smallholders’ oil palm derived from logged forest; that is the land changed in status from forest to oil palm plantation. The other 53% of oil palm area derived from non-forested land. The land use history before the establishment of independent smallholder oil palm mostly comprised general-purpose field activities and former forest-felling (forest concessions). The land cover before conversion into oil palm comprised rubber plantation, secondary forest, and shrub cover. From the results of our survey, we conclude that most of the oil palm plantations planted between 1990 and 2002 have their origins not in primary forest, but rather in degraded secondary forest, former fields, and shrub-land. These results imply that conversion of forest area into oil palm plantations is not the direct cause of deforestation in the tropical forests of Kampar, Riau Province.